Floating elementary osmotic pump tablet (FEOPT) for controlled delivery of diethylcarbamazine citrate: A water-soluble drug - Khan Z.A.; Tripathi R.; Mishra B. (My University, 2025)
The present work investigates the feasibility of the design of a novel floating elementary osmotic pump tablet (FEOPT) to prolong the gastric residence of a highly water-soluble drug. Diethylcarbamazine citrate (DEC) was chosen as a model drug. The FEOPT consisted of an osmotic core (DEC, mannitol, and hydrophilic polymers) coated with a semipermeable layer (cellulose acetate) and a gas-generating gelling layer (sodium bicarbonate, hydrophilic polymers) followed by a polymeric film (Eudragit RL 30D). The effect of formulation variables such as concentration of polymers, types of diluent, and coat thickness of semipermeable membrane was evaluated in terms of physical parameters, floating lag time, duration of floatation, and in vitro drug release. The Fourier transform infrared and X-ray diffraction analysis were carried out to study the physicochemical changes in the drug excipients powder blend. The integrity of the orifice and polymeric film layer was confirmed from scanning electron microscopy image. All the developed FEOPT showed floating lag time of less than 8 min and floating duration of 24 h. A zero-order drug release could be attained for DEC. The formulations were found to be stable up to 3 months of stability testing at 40°C/75% relative humidity. © 2011 American Association of Pharmaceutical Scientists.